The energetics and interactions of random dislocation walls - Zaiser, Michael (Philosophical Magazine Letters, 2013)
Regular dislocation walls, where dislocations are spaced equally along the wall direction, are a popular idealization for modelling the arrangement and interactions of excess dislocations in plastic deformation. The assumption of regular walls is motivated by the fact that such walls represent minimum energy arrangements for dislocations of the same sign, and it allows to use the analytically known short-ranged stress fields of such walls for analyzing the structure of plastic boundary layers. In order to critically evaluate the physical robustness of models based on regular walls, we investigate their random counterparts and demonstrate that the energetics and interactions of such non-periodic dislocation arrangements differ completely from the periodic wall arrangements. Implications of our results for the modelling of plastic boundary layers and dislocation-grain boundary interactions are discussed.
Keywords: plasticity of crystals; dislocation theory; dislocation interactions